Nurses' Perceptions of Self as Role Models of Health. (August 2018) - Hurley, Shelia; Edwards, Joellen; Cupp, Jann; Phillips, Michael
This study purposed to determine the relationship between nurses' personal health practices and their perceptions of themselves as role models for health promotion, and assess the relationship of personal and professional characteristics both on perception of self as role model and on the practice of healthy behaviors. In this study of 804 Tennessee registered nurses, 4% report smoking, 24.9% drink alcohol, 34% are overweight, and 30% are obese. Approximately 70% do not meet the weekly physical activity recommendations of 150 min, and 36.2% follow guidelines for a healthy diet only 50% of the time or less. There were significant correlations between following a healthy diet or physical activity and the Self as a Role Model of Health Promotion (SARMHEP) scores. Based on the regression analysis, working in an acute care or ambulatory setting negatively affected the SARMHEP, as opposed to age and sex having a positive effect on the SARMHEP score.